Mitochondrial genome of Hormaphis betulae and its comparative analysis with Pseudoregma bambucicola (Hemiptera: Hormaphidinae). Issue 1 (2nd January 2020) - Nong, Xiang; Liu, Yunjian; Wang, Lidan; Zhong, Shengnan; Yu, Xiaobo; Xie, Yue
Abstract: Hormaphis betulae (Hemiptera: Hormaphidinae) is a common aphid of birch plants. Here, the complete mitochondrial genome sequence of a representative of this aphid from China was determined using next generation sequencing platform. The genome was 15, 129 bp in length and encoded 13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes. The phylogeny revealed that two Chinese isolates of H. betulae clustered together and formed a monophyletic relationship with Pseudoregma bambucicola in the subfamily Hormaphidinae, supporting their species validity in Aphididae. The cumulative mitochondrial DNA data provides a better understanding of the phylogenetic relationship of this species in plant aphids.